Chloroplast characterizations and phylogenetic location of a common ornamental cherry cultivar, Prunus campanulata 'Kanhizakura-plena' (Rosaceae). Issue 2 (3rd July 2019) - Zhou, Yuzhen; Zheng, Yan; Chen, Bin; Wei, Ziling; Lin, Weijie; Zhao, Kai
Abstract: Flowering cherries are well-grown in the world to develop a gorgeous landscape. Though several species are sequenced, there is huge mass of genome-level aberrances between wild species and highly domesticated cultivars. Herein, we established the complete chloroplast genome of Prunus campanulata 'Kanhizakura-plena'. The chloroplast genome circle (157948 bp) was formed by an 85949 bp large single-copy (LSC) region, a 19127 bp small single-copy (SSC) region, and 2 inverted repeat (IRs) regions of 26436 bp. Independent annotation showed 124 genes were found and conserved tRNA genes and rRNA genes were 37 and 8, respectively. The overall GC content was 36.72%, same with the known species, P. campanulata . Phylogenetic tree confirmed the relationship that P. campanulata 'Kanhizakura-plena' is most closely related to P. campanulata, nested inside Prunus. This announcement of chloroplast genome helps genetic modification and phylogenetic study in Prunus genus with useful information. It is a valuable resource for further breeding.